MENINGKATKAN MOTIVASI KERJA GURU MELALUI PEMBERIAN REWARD DAN PUNISHMENT - Zuhdiah Zuhdiah (Vidya Karya, 2019)
Abstract. This study aims to improve teacher motivation performance in Banjarmasin PGRI 9 Junior High School through reward and punishment methods. There are 5 parameters used to measure teacher performance improvement. This study is a School Action Research (SAR) that uses 2 cycles of activity. The study subjects were 15 subject teachers of SMP PGRI 9 Banjarmasin. The research instrument used observation sheets, questionnaires, and documentation. The data were analyzed using percentage techniques. The results of the study showed that by using the reward and punishment actions given by the school principal, there had been an increase in teacher performance in terms of (1) The duration of completion of teaching and learning in class from 70% in the first cycle to 85% in the second cycle; (2) Achieving student achievement targets, from 60% to 80%; (3) Teacher attendance on time from 60% to 86%; (4) Teacher administration completeness from 60% to 85%; and (5) The duration of teaching activities from 70% to 85%.  .Keywords: motivation, teacher performance, reward and punishment Abstrak. Penelitian ini bertujuan meningkatkan motivasi kinerja guru di SMP PGRI 9 melalui metode pemberian reward dan punishment. Ada 5 (lima) parameter yang digunakan untuk mengukur peningkatan kinerja guru. Penelitian ini merupakan Penelitian Tindakan Sekolah (PTS) yang menggunakan 2 siklus kegiatan. Subyek penelitian adalah 15 orang guru mata pelajaran di SMP PGRI 9 Banjarmasin. Instrumen penelitian menggunakan lembar observasi, angket, dan dokumentasi. Data dianalisis mengunakan teknik persentase. Hasil penelitian menunjukkan bahwa dengan menggunakan tindakan reward dan punishment yang diberikan kepala sekolah telah terjadi peningkatan kinerja guru dalam hal (1) Durasi penyelesaian mengajar KBM dikelas dari 70% pada siklus pertama menjadi 85% pada siklus kedua; (2) Pencapaian target prestasi siswa, dari 60% menjadi 80%; (3) Kehadiran guru tepat waktu dari 60% menjadi 86%; (4) Kelengkapan administrasi guru dari 60% menjadi 85%; dan (5) Durasi kegiatan mengajar dari 70% menjadi 85%.  Kata kunci: motivasi, kinerja guru, reward dan punishment